(untitled) (Bangladesh Journal of Medical Science, 2022)
Background: COVID-19 is a rapidly spreading communicable disease worldwide. It varies widely in its spectrum of manifestations, from being mild self-limiting disease, to fulminant disease, often leading to complications and death. Diabetes is an important co-morbidity linked to severity of infection by SARSCoV- 2, which predisposes them to severe pneumonia. Poor glycaemic control is associated with worse outcomes. The disease burden of COVID-19 is continuously increasing, and with a high prevalence of diabetes, it is all the more important to understand the vital aspects of COVID-19 infection in diabetic population. Hence, we try to provide close insights into its pathophysiology, clinical characteristics, recommendations on management and prevention and possible avenues for improving disease outcomes. Methods: PubMed database and Google Scholar were searched using the key terms ‘COVID-19’, ‘SARS CoV- 2’, ‘Corona’ and ‘diabetes’. Full texts of the retrieved articles were accessed and referred. Three main mechanisms which influence COVID-19 disease manifestation in diabetics include: (a) Entry of virus via ACE-2 receptors (b) Action through Dipeptidyl-peptidase-4, and (c) Elevation of glucose concentration in airways by elevated blood glucose.ACE-2 is expressed in alveolar epithelial cells, heart, renal-tubular and intestinal epithelia and pancreas. S-Glycoprotein on the surface of SARS-CoV-2 binds to this ACE-2 and undergoes a conformational change. This allows its’ proteolytic digestion by host cell proteases TMPRSS2 and Furin, leading to internalization of virus. Viral entry into cells triggers an inflammatory response by T-helper-cells and at times, a ‘cytokine storm’, resulting in organ damage. Apart from diminishing neutrophil chemotaxis and reducing phagocytosis, by which diabetes predisposes individuals to infections, there are several specific factors with respect to SARS-CoV2: (i) Increased ACE-2 expression (ii) Raised Furin (iii) Diminished T-cell functioning, and (iv) Increased IL-6 levels. Movement restrictions, increased stress due to social isolation and lack of physical activity further complicates the issue. It is therefore, much essential to raise awareness among front-line workers. Finally, the current situation emphasizes the need for more clinical investigation and define best practices for optimum outcomes. Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 19-23